Freshwater ecology : concepts and environmental application - Dodds, Walter K (Academic Press / San Diego, 2002)
Why study continental aquatic systems; Properties of water; Movement of light, heat, and chemicals in water; Hydrology and physiography of grounwater and wetland habitats; physiography of flowing, water, Physiography of lakes and reservoir